2013
DOI: 10.1111/pedi.12078
|View full text |Cite
|
Sign up to set email alerts
|

Testicular function during adolescence in boys with type 1 diabetes mellitus (T1D): absence of hypogonadism and differences in endocrine profile at the beginning and end of puberty

Abstract: Adolescents with T1D do not exhibit hypogonadism, as shown by normal gonadotropin, testosterone, inhibin B, and AMH levels. However, in T1D boys, HbA1c and BMI-SDS had a negative association with testosterone levels. Elevated testosterone levels are observed during late puberty, which were not present earlier.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
5
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 59 publications
(79 reference statements)
1
5
0
1
Order By: Relevance
“…One mechanism that may explain this finding could be the higher testosterone levels present at the end of puberty in boys with T1D. Rocha et al showed that adolescents with T1D have elevated testosterone levels only at the final stages of puberty and not at the beginning of pubertal development, which agrees with the findings of our study …”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…One mechanism that may explain this finding could be the higher testosterone levels present at the end of puberty in boys with T1D. Rocha et al showed that adolescents with T1D have elevated testosterone levels only at the final stages of puberty and not at the beginning of pubertal development, which agrees with the findings of our study …”
Section: Discussionsupporting
confidence: 93%
“…The fact that the final stages of puberty were observed in younger T1D than C adolescents, although they had similar ages at the initial stages of puberty, suggests that the duration of puberty may be shorter in the former group. A possible mechanism explaining the shorter duration of puberty in boys with T1D could be the higher testosterone levels observed at the final stages of puberty in T1D boys . T1D adolescents were shorter than C at the end of puberty, suggesting that they had a lower pubertal growth spurt.…”
Section: Discussionmentioning
confidence: 99%
“…AMH is potentially an important marker for congenital secondary hypogonadism among adults and delayed puberty in adolescents [54]. In fact, around the time of puberty, Sertoli cells mature, whereas AMH levels decline due to an increased level of intratesticular testosterone, which inhibits AMH production [55]. The relationship between insulin resistance and hypogonadism, as reflected by free testosterone levels, is shown to be bidirectional among men.…”
Section: Discussionmentioning
confidence: 99%
“…Adult and adolescent males with T1D are reported to have lower IS, independent of obesity‐status, than normal controls . Moreover, puberty is characterized by endocrine changes associated with deterioration in metabolic control and worsening IS .…”
mentioning
confidence: 99%